A good gay Odyssey: Andrew Sean Greer's Less. (3rd July 2021) - Fletcher, Judith
Abstract: Andrew Sean Greer's comedic novel Less is a self-reflexive version of the Odyssey, featuring a gay love story in which the narrator and his subject merge to produce a postmodern homophrosyne that recapitulates the like-mindedness of Odysseus and Penelope. Although the novel makes explicit allusions to specific events and characters of the Homeric epic, its most significant intertextuality is not inscribed in Less's events and characters, but rather in their telling, as if by a male Penelope to whom Odysseus recounted his tales. Using the device of the mise-en-abyme, and yet disrupting the conventions of novelistic story-telling, Greer aligns the recursive structures of his text in order to intertwine theories of narratology with sexual identity.